12.5k views
4 votes
2x/3 - x/6 = -3/4

How do I solve this linear equation?

User Jarl
by
4.4k points

2 Answers

1 vote

Answer:

x = - 1.5

Explanation:

Given


(2x)/(3) -
(x)/(6) = -
(3)/(4)

Eliminate the fractions by multiplying by the lowest common multiple of the denominators 3, 6 and 4, that is 12

Multiply each term by 12

12 ×
(2x)/(3) - 12 ×
(x)/(6) = - 12 ×
(3)/(4)

8x - 2x = - 9

6x = - 9 ( divide both sides by 6 )

x = -
(9)/(6) = -
(3)/(2) = - 1.5

User Krads
by
4.8k points
4 votes
first you would combine like terms. you would do this by finding the common denominator of 2x/3 and 1x/6 so that you can subtract them. since the least common multiple of 3 and 6 is 6, the fractions would become 4x/6 and 1x/6. subtracting those would leave you with 3x/6 = -3/4. then, you would multiply both sides by the reciprocal, or 6/3 aka 2. by doing that, you get x = -6/4, or -3/2.
User Musica
by
5.1k points